THE ANALYSIS OF EUPHEMISMS RELATED TO POLITICAL CORRECTNESS IN ENGLISH AND UZBEK POLITICAL PRESS (Conferencea, 2022)
Nowadays political correctness is one of the approach in linguistics and means not allowing any discrimination in speech activity, and not using awkward expressions. To express this political correctness we use words and word combinations which serve to describe the object of speech in a softer, more subtle way rather than expressing it directly and openly. Euphemism is one of the way of expressing political correctness. This article analyzes the structure of the euphemism related to political correctness in English and Uzbek languages.